Tinjauan Historis terhadap Eksistensi dan Perkembangan Efraim - Pontas Surya Fernandes (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2021)
This article discusses several important matters relating to Ephraim as a representation of the Northern Kingdom. This Northern Kingdom is closely related to the ministry of the prophet Hosea, as the man sent by God to call for the conversion of the king. With a historical descriptive approach, it shows how the historical conditions and position of Ephraim in Israel were, as well as showing the social, political, economic, and religious conditions. Thus the comprehensive development of Efraim was obtained.AbstrakArtikel ini membahas beberapa hal penting yang berkaitan dengan Efraim sebagai representasi Kerajaan Utara. Kerajaan Utara ini sangat terkait dengan pelayanan nabi Hosea, sebagai orang yang diutus Tuhan untuk menyerukan pertobatan raja. Dengan pendekatan deskriptif historis ditunjukkan bagaimana kondisi sejarah dan posisi Efraim di Israel, selain juga memperlihatkan keadaan sosial, politik, ekonomi, dan agama. Dengan demikian diperoleh perkembangan Efraim secara komprehensif.